Leaf anatomical study of Onosma (Section Onosma, Subsection Haplotricha) Boraginaceae in Iran - Jamshidi, Reyhaneh; Keshavarzi, Maryam; Mehrabian, Ahmad Reza (Acta Biologica Szegediensis, 2026)
The genus Onosma (Boraginaceae) comprises a diverse group of species with significant taxonomic complexity. In this study, the leaf anatomical characteristics of 11 species from the Onosma section, Haplotricha subsection in Iran were examined to identify diagnostic traits that contribute to their classification. The qualitative and quantitative anatomical features were statistically analyzed. Multivariate statistical analyses, such as cluster analysis and principal component analysis, were used to determine species relationships based on the variations in the anatomical traits. The results revealed distinct variations among species, with O. assadii and O. sabalanica showing the highest divergence. Factor analysis indicated that mesophyll structure, midrib thickness, and trichome characteristics were key differentiating features. These findings support the significance of leaf anatomical traits in the systematic study of Onosma and contribute to a more refined taxonomic framework for the genus.